Effectiveness and implementation of an online intervention (MINDxYOU) for reducing stress and promote mental health among healthcare workers in Spain: a study protocol for a stepped-wedge cluster randomized trial - Yolanda López-; Selene Fernández-Martínez; Adrián Pérez-Aranda; Alberto Barceló-Soler; Jose Guzman-Parra; Esperanza Varela-Moreno; Daniel Campos; Alicia Monreal-Bartolomé; María Beltrán-Ruiz; Berta Moreno-Küstner; Fermín Mayoral-Cleries; Javier García-Campayo (BMC, 2022)
Abstract Background The World Health Organization has formally recognized that healthcare professionals are at risk of developing mental health problems; finding ways to reduce their stress is mandatory to improve both their quality of life and, indirectly, their job performance. In recent years, particularly since the COVID-19 pandemic outbreak, there has been a proliferation of online interventions with promising results. The purpose of the present study is twofold: to test the effectiveness of an online, self-guided intervention, MINDxYOU, to reduce the stress levels of healthcare workers; and to conduct an implementation study of this intervention. Additionally, an economic evaluation of the intervention will be conducted. Methods The current study has a hybrid effectiveness-implementation type 2 design. A stepped wedge cluster randomized trial design will be used, with a cohort of 180 healthcare workers recruited in two Spanish provinces (Malaga and Zaragoza). The recruitment stage will commence in October 2022. Frontline health workers who provide direct care to people in a hospital, primary care center, or nursing home setting in both regions will participate. The effectiveness of the intervention will be studied, with perceived stress as the main outcome (Perceived Stress Scale), while other psychopathological symptoms and process variables (e.g., mindfulness, compassion, resilience, and psychological flexibility) will be also assessed as secondary outcomes. The implementation study will include analysis of feasibility, acceptability, adoption, appropriateness, fidelity, penetration, and sustainability. The incremental costs and benefits, in terms of quality-adjusted life years, will be examined by means of cost-utility and cost-effectiveness analyses. Discussion MINDxYOU is designed to reduce healthcare workers' stress levels through the practice of mindfulness, acceptance, and compassion, with a special focus on how to apply these skills to healthy habits and considering the particular stressors that these professionals face on a daily basis. The present study will show how implementation studies are useful for establishing the framework in which to address barriers to and promote facilitators for acceptability, appropriateness, adoption, feasibility, fidelity, penetration, and sustainability of online interventions. The ultimate goal is to reduce the research-to-practice gap. Trial registration This study was registered in ClinicalTrials.gov on 29/06/2022; registration number: NCT05436717.